Examining the causal model of teachers' negligence based on organizational silence by organizational indifference mediation - Ebrahim Aryani ghizghapan; adel zahed bablan; reyhaneh abbaspoor; behzad moradi (Allameh Tabataba'i University Press, 2017)
The purpose of this study was examining the causal model of teachers' negligence based on organizational silence by organizational indifference mediation. Methodology of the research in terms of the main strategy, was quantitative, in terms of the strategy, was field, and in terms of analytical, was descriptive-correlation.The statistical population consisted of teachers of the Mahabad town in the academic year 2017-2018 with a capacity of 459 person. The sampling method was random. The sample size according to the Kregci-Morgan model and with error α = 0/05, was considered 207 persons. To collect data, organizational negligence questionnaire (SOP) (with reliability α = 0/87), Organizational silence (OSQ) (with reliability α = 0/84) and organizational indifference questionnaire (OIQ) (with reliability α = 0/78), were used. Validity of the tools was confirmed by the professors of education and psychology. Data were analyzed using two software's Spss vs. 22 and lisrel. 8/50 and analyzed by structural equation modeling. The results showed that the proposed model had suitable fit (x2/df=2/99, GFI=0/92, AGFI=0/92, CFI=0/91, NFI=0/93, RMSEA=0/064) and the component of organizational silence has a direct and indirect effect through the component of organizational indifference on organizational oversight (P<0/05). In order to answer the education organization as much as possible to the needs of teachers and to meet the challenges of organizational development, it is suggested that efforts to improve teachers' abilities and the removal of their silence and organizational indifference be proposed as a serious priority on the agenda, to reduce the amount of employee negligence